ANALISIS FRAMING PEMBERITAAN STAF KHUSUS MILENIAL JOKOWI PADA TEMPO.CO - Sonia Lase, Silvy Mercy Ruth; Purnawan, Ni Luh Ramaswati; Pradipta, Ade Devia (E-Jurnal Medium; Vol 2 No 1 (2021): Jurnal Ilmu Komunikasi Vol 2 No 1 Tahun 2021, 2021)
The millennial presidential expert staff became the public spotlight after being officially introduced by Jokowi on November 21, 2019. This is the first time young people were in the state palace. The joining of millennial expert staff in the government has become a growing issue and has been widely reported by the mass media. This study aims to identify and describe the news framing of millennial expert staff at tempo.co. The qualitative descriptive approach was used in this study with Robert Entman's framing analysis method. The data source for this research is tempo.co online news for the period 22 November 2019 – 25 November 2019. The results of this study indicate that the framing by tempo.co to form public opinions on the news of millennial expert staff divided into four major issues by presenting news reports repeatedly .   Keywords: Framing Analysis Robert Entman, Staf Khusus Milenial¸ Tempo.co